2016
DOI: 10.3389/fmicb.2016.02027
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G-Mediated G-to-A Hypermutation of the HIV-1 Genome: The Missing Link in Antiviral Molecular Mechanisms

Abstract: APOBEC3G (A3G) is a member of the cellular polynucleotide cytidine deaminases, which catalyze the deamination of cytosine (dC) to uracil (dU) in single-stranded DNA. These enzymes potently inhibit the replication of a variety of retroviruses and retrotransposons, including HIV-1. A3G is incorporated into vif-deficient HIV-1 virions and targets viral reverse transcripts, particularly minus-stranded DNA products, in newly infected cells. It is well established that the enzymatic activity of A3G is closely correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 91 publications
0
39
0
Order By: Relevance
“…HIV-1 replication is characterized by rapid and highly error-prone reverse transcription, which lacks proofreading capacity and causes genetic defects in viral genomes (15,(36)(37)(38)(39)(40). Also, an antiviral mechanism called G-to-A hypermutation renders in-frame stop codons and produces replication-deficient HIV-1 DNA during reverse transcription (15,41,42). These genetic defects have been identified in memory T cells during therapy (43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 replication is characterized by rapid and highly error-prone reverse transcription, which lacks proofreading capacity and causes genetic defects in viral genomes (15,(36)(37)(38)(39)(40). Also, an antiviral mechanism called G-to-A hypermutation renders in-frame stop codons and produces replication-deficient HIV-1 DNA during reverse transcription (15,41,42). These genetic defects have been identified in memory T cells during therapy (43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…The "pre-existed" expression of these host factors guarantees a more rapid response and a direct inhibition of viral infection [10,25]. For example, the cytidine deaminase, apolipoprotein editing complex 3 G (APOBEC3G), introduces transversion mutations into the HIV genome, thereby impeding HIV infection [26]. It is well established for how innate immunity responds to VSV infection; however, the intrinsic immune response to VSV is still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…6 It was shown that A3G efficiently binds ssDNA and restricts retroviruses with deamination-dependent and deamination-independent restriction pathways. 1,[7][8][9][10][11][12] A3G has two domains with Z-dependent motifs: the C terminal domain (CTD), which is catalytically active, and the N-terminal domain (NTD), which is responsible for ssDNA binding. 13 Both domains contribute to the anti-retroviral activity during the viral replication cycle.…”
Section: Introductionmentioning
confidence: 99%